Mechanisms of action of metformin in type 2 diabetes: Effects on mitochondria and leukocyte-endothelium interactions - Apostolova, Nadezda (Redox Biol, 2020)
Type 2 diabetes (T2D) is a very prevalent, multisystemic, chronic metabolic disorder closely related to atherosclerosis and cardiovascular diseases. It is characterised by mitochondrial dysfunction and the presence of oxidative stress. Metformin is one of the safest and most effective anti-hyperglycaemic agents currently employed as first-line oral therapy for T2D. It has demonstrated additional beneficial effects, unrelated to its hypoglycaemic action, on weight loss and several diseases, such as cancer, cardiovascular disorders and metabolic diseases, including thyroid diseases. Despite the vast clinical experience gained over several decades of use, the mechanism of action of metformin is still not fully understood. This review provides an overview of the existing literature concerning the beneficial mitochondrial and vascular effects of metformin, which it exerts by diminishing oxidative stress and reducing leukocyte-endothelium interactions. Specifically, we describe the molecular mechanisms involved in metformin's effect on gluconeogenesis, its capacity to interfere with major metabolic pathways (AMPK and mTORC1), its action on mitochondria and its antioxidant effects. We also discuss potential targets for therapeutic intervention based on these molecular actions.